The Impact of Participatory Design in Enhancing the Vitality of Urban Space - Shyaa, Athraa; Basee, Dheah H. (Al-Nahrain Journal for Engineering Sciences, 2025)
The paper focuses on the role of participatory design and its various methods—such as awareness methods, social interaction methods, as well as indirect and open methods— that involve all citizens in the process of design, implementation, and future development process. The architect's role in this process is to transform the desires and visions of the participants into a practical reality, ensuring that their needs are met to create vibrant spaces. This involves achieving specific indicators that generate vitality in these spaces, including diversity, communication opportunities, strong identity, concentrated density, accessibility, and safety, all of which enhance social interaction. The paper referred to a number of international examples in Norway and Denmark, and Arab examples in Jordan that proved the effectiveness of the participatory approach in achieving vital environments. Hence, the research problem is represented by the following questions: How does participatory design contribute to enhancing the vitality of the space? To what extent is the participatory design methodology applied to enhance vitality and help achieve a sense of belonging within the space? The paper findings emphasized the importance of participatory design in meeting the needs of the local community and in creating a vital, safe, and inclusive environment characterized by social cohesion, cooperation, ownership, belonging, and equality. This highlights the importance of encouraging the entire community to engage in the design process, which can lead to creative ideas and empower citizens. The paper recommends adopting the participatory design approach to improve the quality of life and enhance the vitality of urban spaces.